Celiac-Associated Autoimmune Thyroid Disease: A Study of 16 Patients with Overt Hypothyroidism - Hugh J Freeman (Canadian Journal of Gastroenterology)
Previous reports have suggested that autoimmune thyroid disorders (including Hashimoto’s or lymphocytic thyroiditis) may occur in patients with celiac disease. In this study, the prevalence of thyroid disease was explored in a series of 96 consecutive patients seen with biopsy-defined adult celiac disease (average age 47.3 years). Sixteen celiac patients (average age 58.1 years) were detected with hypothyroidism, including four treated with radio-iodine ablation or thyroidectomy for Grave’s disease. In addition to celiac disease, almost half had dermatitis herpetiformis, a small intestinal neoplasm (particularly lymphoma) or both. Diagnosis of thyroid disease preceded diagnosis of celiac disease in 13 patients or was made concurrently in two patients. In only one patient was thyroid disease detected after celiac disease was diagnosed. This indicates that thyroid diseases occur more commonly in celiac disease than is currently appreciated, possibly due to shared embryological origins or common immunopathological features, and may be the presenting clinical manifestation in adults especially if there is coexistent dermatitis herpetiformis. Careful monitoring of this subgroup may be warranted because of the frequency of neoplastic intestinal diseases, particularly lymphoma.